How Does the Design of the Level Influence Stealth in Games - Yeap, Paul Lin Xiao (2020)
Our game “ Struck by Oil” is a stealth game that uses a third-person camera where the player will play as “Orang Minyak” a mythical creature in Malaysian folklore, which the objective is to break into people’s houses to steal a list of items. The player will have to avoid the NPC’s or non-playable characters from catching them by hiding in dark places or to throw items such as a glass